Empirical Analysis on Performance of Mergers and Acquisitions Activity of Chinese List Companies - Hu, Baohan (2017)
this dissertation is based on primarily factor analysis method so as to find out the factors on which influencing the performance of mergers and acquisitions. data is derived mostly from CSMAR. the performance of Merger and acquisitions listed companies is tested, the period of data is from 2012 to 2016. the companies's performance before and after M&As are compared to improve the reliability of this dissertation. main literature including "The post‐merger performance of acquiring firm" by Agrawal (1992), "The anatomy of a merger" by Buono (1985), and so on are mainly adopted.